(untitled) (Journal of Oriental Studies, 2021)
After the settlement of of Sufism among the Turkic society have occurred many important events in the life of Turks. It was created wonderful examples of the Turkic Sufi culture in social areas as language, literature, art, philosophy, music and many others. So, find to investigate and present to people and scientific community works reflecting the Sufi culture and belonging to eminent persons to occupy an important place in Turkish-Islamic history, is considered an important work in preserving and delivering our national culture and spiritual values to the next generation. In the history of Sufism, many works have been written about the lives and activities of the representatives of the sect. Among them are many works by Khoja Abdulhaliq Gijduvani, such as Maqamat-i Khoja Yusuf-i Hemedani, Khoja Ishaq’s «Hadiqat ul-Arifin» and Sultan Ahmad Mahmud Hazini’s «Jawahir ul-ebrar min emwaj il-bihar». Didactic works such as this, which express the life and morals of highly spiritual personalities, are important examples of religious and mystical culture. In recent years, done a lot of research on the life and opinions of Khoja Ahmad Yassawiy, was discovered some new sources. Despite this, in many libraries have many more books on Khoja Ahmad Yassawiy and Yassawism schools that are not yet studies. Many legends, stories and narrations about Khoja Ahmad Yassawiy took place in folk literature and written culture and literature examples. Among such works, Imam Husomiddin Sighnoqiy’s «Risola dar tarjima-i Ahmad Yassawiy» has a special importance, which is kepted on hand-written storehouse of Institute Oriental studies of name Abu Rayhan Beruniy at the Academy of Sciences of Republic Uzbekistan. In this article, we will try to introduce and analyze this book. Such works have value in terms of the spiritual, social, cultural function of the sects in the society, the relations between the sheikh and the disciple, reflecting the intellectual dimension of Sufism, and following the legacy of the predecessors. Key words: Sufism, Khoja Ahmad Yassawii, Yassawism, Wisdom, Order, Turkestan.